WOUND HEALING ACTIVITY OF BINAHONG LEAF EXTRACT NANOGEL ON ORAL TISSUES - HANAFIAH, OLIVIA AVRIYANTI; SATRIA, DENNY; HARAHAP, AMI ANGELA; DOHUDE, GOSTRY ALDICA; LESTARI, CHANDRA; BERNARD; HG, AFIFAH AYUNI.; FAJAR, TASYFINA HANNAN; KURNIA, HARRY (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of the present study is to formulate and evaluate a topical gel containing minoxidil and tofacitinib citrate for alopecia areata. Methods: Forty-eight rat males were given treatment using 3% binahong leaf extract nanogel (twelve rats given palatal wound, twelve rats mandibular tooth extraction) and nanogel base (same with the amount used to extract). On palatal wounds, as many as four rats were in euthanasia on days third, seven, and fourteen for each group treatment. Whereas on the extraction groups, four rats were in euthanasia on days seventh, fourteen, and twenty-eight. palatal tissue and alveolar bone were taken, and fibroblasts as well as osteoblasts were observed using the coloring Hematoxylin-eosin. Results: Data revealed there were significant differences in the number of fibroblasts in each treatment between day three and seven (p<0.05), between day seven and fourteen (p<0.05), and there were significant differences in the number of osteoblasts in each treatment for 3 periods (p<0.05). Conclusion: Application of binahong leaf extract nanogel on palatal wound increased fibroblast proliferation and on post-extraction socket increased the number osteoblasts indicating better wound healing compared to control.